Pengaruh Model Numbered Head Together Terhadap Hasil Belajar PKn Kelas IV Sekolah Dasar - Rahma Yuni, Shari Ayu; Reinita, Reinita; Mayarnimar, Mayarnimar (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2014)
This research aims at finding out the effects of applying the NHT model toward the students’ learning outcomes of civics subject at class IV. This quasi experiment used the non-equivalent control group design. The population was all 4th grade students of SDN 10 Bandar Buat. Samples were chosen by using the saturation sampling technique in which IVA acted as the experimental class and IVB as the control one. The research result shows that by using t-test with the level of significant of 0,05, tcount=2,1 >ttable=2,01 with the mean score of the mean score of the score of the experimental class = 80,9 and the control class = 75,86. Thus, the H1 hypothesis is accepted.